2014
DOI: 10.1590/s1980-65742014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and maturational predictors of technical performance in young soccer players

Abstract: The purpose of the present study is to describe the association between chronological age, morphology, biological maturation and sport experience in relation to technical performance in young Brazilian soccer players. Technical, maturation and anthropometric variables were assessed in 119 soccer players, 74 and 45 in the under-15 and under-17 categories, respectively. Data were analyzed using a multiple linear regression model. Adiposity was negatively associated with technical performance regardless the age-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 14 publications
5
22
1
11
Order By: Relevance
“…Consequently, in the present study, the players made better decisions regarding the execution of specific defensive motor skills. Thus, another important factor to discuss is the influence of biological maturation on the teaching and learning of techniques [11,32]. The teacher/coach should be aware of the biological advantage that earlier-maturing players can acquire over their peers after the chronological age of 11 years to avoid promoting an unbalanced specialization process in the sport [33].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in the present study, the players made better decisions regarding the execution of specific defensive motor skills. Thus, another important factor to discuss is the influence of biological maturation on the teaching and learning of techniques [11,32]. The teacher/coach should be aware of the biological advantage that earlier-maturing players can acquire over their peers after the chronological age of 11 years to avoid promoting an unbalanced specialization process in the sport [33].…”
Section: Discussionmentioning
confidence: 99%
“…Na temática Metodologias de ensino, 66,4% dos artigos publicados apresentam e/ ou discutem os processos pedagógicos com base na concepção holística, que considera os componentes complexos e dinâmicos do jogo (MESQUITA; PEREIRA; GRAÇA, 2009). Em contrapartida, apenas 33,6% dos artigos desta temática centraram em uma perspectiva meramente técnica, de modo que as análises não abordaram questões táticas (por exemplo, MATTA et al, 2014). Esses dados novamente corroboram certa tendência centrada na visão sistêmica e global de ensino dos JEC no Brasil (RUFINO; DARIDO, 2011).…”
Section: Discussionunclassified
“…Malina et al [73] and Matta et al [74] found that the main predictors that explained the results of skill-related performance (e.g. dribbling, ball control, shooting) were: age, maturation, height, interaction of body height and body mass, and years of training.…”
Section: Other Concernsmentioning
confidence: 99%